Is age a risk factor for liver disease and metabolic alterations in ataxia Telangiectasia patients? - Paulino, Talita Lemos [UNIFESP] (2017)
Background: Ataxia telangiectasia (A-T) is a neurodegenerative disease that leads to mitochondrial dysfunction and oxidative stress. Insulin resistance (IR), type 2 diabetes and the risk for development of cardiovascular disease was recently associated as an extended phenotype of the disease. We aimed to assess IR